The Effect of Background Color on Skin Color Variation of Juvenile Plectropomus leopardus - Feibiao Song; Liping Shi; Fucheng Yao; Yue Gu; Da Zheng; Weiwei Zhang; Yesong Liang; Kaixi Zhang; Min Yang; Lei Wang; Junlong Sun; Jian Luo (Animals, 2022)
Fish skin color is usually strongly affected by the background color of their environment. The study investigated the effects of five different background colors on the skin color of leopard coral groupers (Plectropomus leopardus). More than 450 juveniles were reared in Blue, Red, Black, White, and Transparent background tanks for 56 days. The paraffin section showed that the skin melanin zone of fish in the White group was smaller, whereas the Black and Red groups (especially Black) were nearly the largest. The apparent skin color of P. leopardus was red on the white background, which darkened in response to the other color backgrounds. The Black group revealed the blackest skin color, followed by the transparent group. Moreover, the White group had the highest L*, a*, and b* values. The melanin content and tyrosinase activity in the dorsal and ventral skin of the Black group were significantly higher than those in the other groups (p < 0.05), and the serum α-MSH level was higher in the Black group as well. The carotenoid and lutein contents showed completely different trends among the experimental groups, as carotenoid content was higher in the Red and White groups, while lutein content was higher in the Transparent group. The expression level of scarb1 was highest in the Blue and White groups, followed by the Transparent group, and lowest in the Black group (p < 0.05). The expression trend of scarb1 was similar to the skin color in different backgrounds, indicating that the background color regulated scarb1 expression level through visual center, then influenced the uptake and transport of carotenoids, then influenced the skin color formation of P. leopardus. Moreover, lighter colors inhibited the formation of melanocytes and had a significant effect on carotenoid and lutein contents. Pigment-related genes were involved in the regulation of fish skin color, and they were affected by background color in P. leopardus. These results indicate that a white background is more conducive to maintaining red skin color in juvenile P. leopardus.